Analisis Sistem Informasi Akuntansi Terhadap Efektivitas Penagihan Piutang PT. Sukses Sejahtera Bersama Indonesia - Dewi Sinta; Siti Sundari (CV. KAMPUS AKADEMIK PUBLISING, 2024)
A credit sales accounting information system is needed to improve the receivables collection process to minimize the occurrence of uncollectible receivables. This research aims to examine the credit sales information system of PT. Prosperous Success with Indonesia in effectively collecting receivables. This research uses a qualitative descriptive method by collecting data through observation, interviews and documentation. The receivables collection process is carried out in accordance with the Billing Document Attachment. Documents required in this process include invoices, tax invoices, travel documents, and purchase orders. In this research it can be concluded that the Credit Sales Accounting Information System in the receivables collection process at PT. Sukses Sejahtera Bersama Indonesia is not yet fully effective because problems often occur in the receivables collection process.